1997
DOI: 10.1002/(sici)1098-2736(199704)34:4<377::aid-tea7>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Common student misconceptions in electrochemistry: Galvanic, electrolytic, and concentration cells

Abstract: This study replicates, with additions, research done by Garnett and Treagust. Garnett and Treagust's interview questions for galvanic and electrolytic cells were used with modifications; concentration cell questions were asked in a similar manner. These questions were administered to 16 introductory college chemistry students after electrochemistry instruction. Student misconceptions most commonly encountered included notions that electrons flow through the salt bridge and electrolyte solutions to complete the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
0
13

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(133 citation statements)
references
References 20 publications
5
115
0
13
Order By: Relevance
“…Sanger and Greenbowe [11] replicated research previously carried out by Garnet and Treagust. Most commonly encountered misconceptions included: notions that electrons flow through the salt bridge and electrolyte solutions; that the plus and minus signs assigned to the electrodes represent net electronic charges; that water is unreactive in the electrolysis of aqueous solutions; and that half-cell potentials can be used to predict the spontaneity of individual half-cells, while galvanic cell potentials are independent of ion concentrations.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…Sanger and Greenbowe [11] replicated research previously carried out by Garnet and Treagust. Most commonly encountered misconceptions included: notions that electrons flow through the salt bridge and electrolyte solutions; that the plus and minus signs assigned to the electrodes represent net electronic charges; that water is unreactive in the electrolysis of aqueous solutions; and that half-cell potentials can be used to predict the spontaneity of individual half-cells, while galvanic cell potentials are independent of ion concentrations.…”
Section: Introductionmentioning
confidence: 67%
“…[49] On the other hand, there are students who demonstrate misconceptions in EC, but are still able to deal successfully with these algorithmic quantitative problems. [11] Finally, non-algorithmic problems place high cognitive demands on the brain, and are therefore much more difficult for students. Tsaparlis carried out a correlation study of the role of various cognitive/psychometric factors/variables in the solution of non-algorithmic quantitative problems in elementary physical chemistry, including EC problems.…”
Section: Problem Solving In Equilibrium Electrochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies related to different disciplines, mostly in chemistry, have shown that instruction involving computer animations can facilitate the understanding of chemical processes at the molecular level. For example, students who had viewed molecular-level computer animations were found less likely to demonstrate the misconception that electrons flow in aqueous solutions without the assistance of ions (Sanger and Greenbowe 1997) than students who had not. In another study, students who viewed animations illustrating the molecular processes of diffusion of perfume molecules in air, and osmosis through a selectively permeable membrane, were less likely to exhibit misconceptions regarding equilibrium, and were less likely to have anthropomorphic views of matter (Sanger et al 2001).…”
Section: Distinguishing Between Static and Dynamic Visualizationsmentioning
confidence: 99%
“…The topic of electrochemistry was chosen for two reasons: convenience and our knowledge of the fact that a significant number of high school students struggle with understanding core concepts related to electrochemical cells (e.g., see Doymus, Karacop, & Simsek, 2010;Sanger & Greenbowe, 1997). The STSPCK (see Appendix) consists of three parts with 30 items.…”
Section: Instruments and Data Collection Proceduresmentioning
confidence: 99%